ANALISIS IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 5 TAHUN 2017 TENTANG PENGELOLAAN DAERAH ALIRAN SUNGAI DI NUSA TENGGARA BARAT - Susanti, Susi; Ichsan, Andi Chairil; Setiawan, Budhy (JURNAL RIMBA LESTARI, 2023)
A watershed is a land area that functions as an ecological unit to collect, store, and channel rainfall to lakes or seas naturally. Effective watershed management requires supportive policies and regulations. This study aims to evaluate the implementation of Regional Regulation No. 5 of 2017 on Watershed Management in West Nusa Tenggara and to formulate planning strategies to optimize the policy's implementation. The research methods included literature review, interviews, and observation. Policy analysis was conducted using four criteria derived from William N. Dunn's theory, while management strategies were formulated using SWOT analysis. The findings indicate that the policy implementation falls under the "low" category with a score of 1.58, deeming it ineffective. The highest-scoring strategy is the Weakness-Opportunities (W-O) strategy, which emphasizes optimizing Government Regulation No. 37 of 2012 and Regional Regulation No. 5 of 2017 to enhance coordination in watershed management. These findings highlight the need for strategic measures to strengthen policy implementation for watershed management in West Nusa Tenggara.